IMPROVING THE CAPACITY OF INPUT PROVISION SERVICES FOR PHARMACEUTICAL MATERIAL INDUSTRY IN LAO CAI PROVINCE - Ngoc Son, Ho; Tuan Tuan, Bui; Thi Huyen, Dinh; Thi Hoa, Nguyen (Journal of Forestry Science and Technology, 2022)
Medicinal plants are important non-timber forest products which receives high priority in investment and development in many northern mountainous provinces, especially Lao Cai province. Planting medicinal herbs has contributed significantly to the income of local ethnic minorities. The demand for input services such as seeds, agricultural materials and credit is increasing. The quality of medicinal herbs also depends much on the quality of input provision services. This study was conducted to evaluate the service delivery capacity of service providers for the medicinal material industry in Lao Cai province. The study was conducted through interviews, group discussions, expert consultations, and field observations in two districts of Bat Xat and Bac Ha of Lao Cai province in 2020. Research results showed that farmers growing medicinal herbs in Lao Cai have an increasing need for loans to invest in growing medicinal herbs but was not yet willing to borrow capital to develop and expand the area of ​​medicinal herbs. Cooperatives and businesses currently have short-term revolving loan needs, and do not have a plan to borrow long-term investment capital. The demand for technical services and other input materials in the development of medicinal herbs increases following the expansion of medicinal material areas. However, the provision capacity of the existing agencies is still very limited. Therefore, it is necessary to pilot and implement the service delivery model in line with the market system development approach in which the suppliers will participate in co-investment with farmers, production and processing cooperatives to ensure sustainability, efficiency, mobilizing resources of the private sector to develop medicinal herbs, expanding product consumption markets, thereby encouraging farmers to invest in expanding and improving production and production quality medicinal products.